FORMS OF TRAINING IN CONTEMPORARY HIGH MEDICAL SCHOOLS - Kapustianska, A.A.; Moisieieva, N.V.; Vakhnenko, A.V.; Rumyantseva, M.O.; Ostrovskaya, G.Yu. (World of Medicine and Biology, 2017)
Recently, the organization and demonstration of master classes, such unique seminars on the exchange of experience, professional skills have become increasingly popular. First of all, young people, especially university students, are interested in acquiring new experience in the master class mode. And this is justified, because with such training there is no strict control over the training. In a free environment, it is convenient not only to master modern skills (be it anthropogenic, intellectual or physical work), but it is important to create new acquaintances, communicate with friends and make fruitful use of your time. Such organization of training emphasizes one of the important qualities of the future model of education that is the value of "talent and ability, understood as having particularly effective means of activity in a particular industry." Thus, the motivation and interest, the enthusiasm of students, doctors and teachers with their own development become the driving force of education. The relevance of the new form of teaching practical skills was used by us during the master classes. By conducting a master class, the teacher never aspires to simply transfer knowledge. He tries to involve participants in the process, make them active. All the tasks of the teacher and his actions are aimed at connecting the imagination of the participants, creating an atmosphere in which they could manifest themselves as creators. The teacher creates an atmosphere of openness, goodwill, mutual respect, co-creation in communication. He works together with everyone, as a participant in the master class is also in search of knowledge and ways of working. The teacher excludes the official evaluation of the work of the participants of the master class, but through socialization, the advertisement of works gives an opportunity for self-assessment, self-correction. Using these explanations will help, in our opinion, ensure quality training and effective holding of master classes as part of the dissemination of the pedagogical experience of workers in the medical educational system, increase the competitiveness of the medical profession, the interest of specialists in the possibility of continuing education and popularization of the medicine, improving professional ethics.